2020
DOI: 10.3390/nu12030667
|View full text |Cite
|
Sign up to set email alerts
|

Association between Body Fatness and Vitamin D3 Status in a Postmenopausal Population

Abstract: Vitamin D is a micronutrient that plays a key role in phosphocalcic metabolism. The postmenopausal population presents a risk of deficiency in this vitamin due to hormonal alterations which, in the case of obesity, would be exacerbated. The objective was to assess the status of vitamin D in a postmenopausal population and determine the relationship of 25-hydroxivitamin D [25(OH)D] and its metabolites with anthropometric parameters. The study included 78 healthy postmenopausal women aged from 44 to 76. The nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…A large portion of the women included in this study were also classified as overweight according to their BMI. A recent study found that postmenopausal women with a higher BMI (>27 kg/m 2 ) had lower levels of 25(OH)D [ 54 ]. This is similar to the results of our study, as serum 25(OH)D decreased over the observational period.…”
Section: Discussionmentioning
confidence: 99%
“…A large portion of the women included in this study were also classified as overweight according to their BMI. A recent study found that postmenopausal women with a higher BMI (>27 kg/m 2 ) had lower levels of 25(OH)D [ 54 ]. This is similar to the results of our study, as serum 25(OH)D decreased over the observational period.…”
Section: Discussionmentioning
confidence: 99%
“…Jansen et al reported that BMI should be considered for better estimation of the loading dose of cholecalciferol needed to treat vitamin D deficiency [ 37 ], but they noted that this does not exclude large interindividual variation in dose response. It is well established that obese people have higher risk for vitamin D deficiency [ 38 , 39 ]; Drincic et al reported that most parsimonious explanations for this is simple dilution of 35-OH-vitD in the larger fat and tissue mass [ 40 ]. They also investigated response to graded cholecalciferol supplementation among obese adults [ 41 ], showing that, in obese patients, the dose of vitamin D should be adjusted considering the body size.…”
Section: Discussionmentioning
confidence: 99%
“…PTH and osteocalcin levels were measured using EIA by colorimetric method (ECLIA, Elecsys 2010 and Modular Analytics E170, Roche Diagnostics, Mannheim, Germany). Vitamin D levels were measured by LC-MS/MS (Acquity UHPLC System I-Class Waters, Milford, USA) [33]. The biochemical values of vitamin D obtained were classified according to the reference values of 25-OH-D in plasma, being sufficiency >30 ng/mL, insufficiency 20-30 ng/mL and deficiency <20 ng/mL for total vitamin D [33].…”
Section: Measurement Of Biochemical Parametersmentioning
confidence: 99%
“…Vitamin D levels were measured by LC-MS/MS (Acquity UHPLC System I-Class Waters, Milford, USA) [33]. The biochemical values of vitamin D obtained were classified according to the reference values of 25-OH-D in plasma, being sufficiency >30 ng/mL, insufficiency 20-30 ng/mL and deficiency <20 ng/mL for total vitamin D [33]. The remaining biochemical parameters such as glucose, urea, uric acid, creatinine, triglycerides, total cholesterol, high density lipoprotein (HDL) and low density lipoprotein (LDL) cholesterol, total proteins, transferrin, albumin, homocysteine, bilirubin and transaminases levels, were determined in the Analysis Unit at the Virgen de las Nieves Hospital, Granada (ECLIA, Elecsys 2010 and Modular Analytics E170, Roche Diagnostics, Mannheim, Germany).…”
Section: Measurement Of Biochemical Parametersmentioning
confidence: 99%